2012
DOI: 10.3109/1061186x.2012.736998
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic enzymes PGK1 and PKM2 as novel transcriptional targets of PPARγ in breast cancer pathophysiology

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is a nuclear receptor and plays important roles in breast cancer cell proliferation. The complexity of the underlying biochemical and molecular mechanisms of breast cancer and the involvement of PPARγ in breast cancer pathophysiology are unclear. In this study, we carried out prediction of the peroxisome proliferator response element (PPRE) motifs in 2332 genes reported to be involved in breast cancer in literature. A total of 178 genes were found to have PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Moreover, important proteins involved in aerobic glycolysis such as Glut1, Hk2, Pgk1, and Idh3a were decreased in tumors. Previous studies demonstrated that activation of Pparg could impair the aerobic glycoysis process via inhibiting Pgk1 and Glut1 function [18,43]. These findings indicated that high-dose DEX-inhibited tumor growth via the reduction of glucose metabolism enzymes expression, which starves the cancer cells of ATP and important amino acids/nucleic acid precursors.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, important proteins involved in aerobic glycolysis such as Glut1, Hk2, Pgk1, and Idh3a were decreased in tumors. Previous studies demonstrated that activation of Pparg could impair the aerobic glycoysis process via inhibiting Pgk1 and Glut1 function [18,43]. These findings indicated that high-dose DEX-inhibited tumor growth via the reduction of glucose metabolism enzymes expression, which starves the cancer cells of ATP and important amino acids/nucleic acid precursors.…”
Section: Discussionmentioning
confidence: 90%
“…PPARγ receptor is a member of the nuclear receptor superfamily which upon ligand activation undergoes heterodimerization with retinoic acid-like receptor (RXR) and is translocated to the nucleus where it recognizes a specific sequence - the peroxisome proliferator response element (PPRE) located within promoters of target genes, and acts as a transcription regulator for genes involved in proliferation, cell differentiation, apoptosis, angiogenesis, inflammation, organogenesis, and lipid and carbohydrate metabolism and energy homeostasis [3-5]. Two isoforms of PPARγ have been identified (PPARγ 1 and PPARγ 2), with a wide tissue distribution among various animal species [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another group of differentially expressed proteins, accounting for 27% in HT29 and 20% in HCT116 cell models, were metabolism‐related proteins and the majority of them were upregulated in HCT116 PPARγ, confirming the well‐established role of PPARγ as a regulator of lipid metabolism and glucose homoeostasis (Robbins and Nie, 2011; Janani and Ranjitha Kumari, 2014). Accordingly, PGK1, a critical enzyme of the glycolytic pathway that has recently been proven as a novel target of PPARγ (Shashni et al., 2012), was downregulated in HT29 sh‐PPARγ and validated by western blotting. Also proteins implicated in cellular/protein fate control were among those differentially expressed both in HT29 sh‐PPARγ (27%) and HCT116 PPARγ (23%), including several heat shock proteins (HSPs).…”
Section: Discussionmentioning
confidence: 96%